A New Kind of Nursing: Walking the labyrinth of Cook County Jail. Issue 2 (1st February 2018) - Gorman, Geraldine
Abstract: This paper examines the application of public health nursing education with an emphasis on the social determinants of health within a correctional facility. The innate tension between public health practice and the punitive nature of correctional confinement is discussed through the perspective of student involvement. Exemplars of unexpected contingencies endemic to this practice setting are provided as are insights gleaned from this pilot collaboration between a college of nursing and a county correctional system.